Sedimentation in the semi-enclosed Batan estuary, Aklan, Philippines. - Casibo, Allysa B
The Batan Bay Estuary (BBE) serves as a productive fishing ground but is vulnerable to the threats of sedimentation. identified as a longstanding issue significantly impacting the livelihoods of the local populace, it is imperative to address the problem promptly. Sedimentation is affected by different interacting factors; hence, data on sediment, hydrographic variables, fishing gears, and bathymetry were gathered in this study. The results revealed a trap collection rate of 0.82±0.44 g cm² d¹, with higher values observed in the channels ranging from 0.10 to 2.37 g cm² d¹. Additionally, very fine sand ( 35.43±4.83g) dominates the estuary, suggesting that currents and tides quickly transport finer sediments. The hydrographical data revealed a semi-diurnal tidal cycle, northwestward current and wind direction, current speed of 0.16-0.17 ms⁻¹, wind speed of 3-4 ms⁻¹,and water temperatures of 28-29℃. Furthermore, key water variables were recorded, including temperatures of 30-31℃, salinity of 30-31 ppt, and turbidity of 0.5-3.0 NTU. These variables were influenced by the current and tidal action, resulting in the uneven distribution. The high turbidity observed in TB (Tinago Bay) suggests its role as a collection basin for sediment from smaller tribularies. Sediments mounds extending from the mouth to the mid-portion of BBE and the forefront of TB were revealed in the bathymetry. Additionally, canal-like structures, likely shaped by underwater currents, were identified along the sides. The highest mound elevation reaches up to 15 m at the mouth of the bay, indicating significant sediment deposition in the study area, particularly in TB, where shallowing was observed. This study confirms that the richest potential source of sediments for BBE is the adjacent coastal areas near the mouth and TB. Tide, current and sediment grain size are the influential factors in sediment transport and accumulation, ultimately impacting the topography of BBE and TB.